Validity of maximum performance tasks to diagnose motor speech disorders in children. - Thoonen G; Maassen B; Gabreels F; Schreuder R (Clinical Linguistics & Phonetics, 1999)
In a previous study a diagnostic procedure was developed to assess motoric involvement in clear cases of developmental apraxia of speech (DAS) and spastic dysarthria, as well as normal-speaking children. The aim of the present study is to cross-validate this diagnostic procedure. To achieve this aim the maximum performance tasks of the protocol, consisting of maximum vowel and fricative prolongation, and maximum syllable repetition, were administered to less clear cases of DAS and spastic dysarthria, children with a speech disorder of unknown origin and newly selected normal-speaking children (total number of children in the study, 72; aged predominantly between 4 and 12 years). The results showed that spastic dysarthria can be diagnosed on the basis of the maximum rate of repetitive sequences ('papa ...', 'tata ...', 'kaka ...') in combination with maximum vowel prolongation. DAS can be diagnosed on the basis of the maximum rate of alternating sequences ('pataka ...') in combination with maximum fricative prolongation. Using the diagnosis of speech-language pathologists as a criterion, sensitivity and specificity values were obtained ranging from 89 to 100%. Among the children with a speech disorder of unknown origin significant dysarthric or apraxic involvement was observed. Thus, it can be concluded that the diagnostic procedure yields quantitative measures of the degree to which dysarthria or apraxia plays a role in the development and maintenance of speech disorders in children.